2004
DOI: 10.1089/152308604771978417
|View full text |Cite
|
Sign up to set email alerts
|

Increased Apoptosis and Expression of p21 and p53 in Premature Infant Baboon Model of Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD) is a major complication of premature infants who receive prolonged ventilatory support. The pathophysiology of BPD involves oxidant injury, baro/volutrauma, and disordered lung repair. Exposure of premature lung that is poorly adapted for air breathing (>3% oxygen in fetal lung) to a higher concentration of oxygen can cause significant oxidant injury. Cell growth and differentiation of the developing lung require selective and ordered cell division. As hyperoxia can increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
(52 reference statements)
4
33
0
Order By: Relevance
“…Pathway analysis of genes in the G2 and BPD overlap showed that the most enriched pathways included the p53 signaling pathway and the complement and coagulation cascades. Previous studies have demonstrated a role for p53 in the development of BPD (30). Among the genes identified in this analysis GTSE1, THBS1, and SERPINE1 act downstream from p53.…”
Section: Discussionmentioning
confidence: 68%
“…Pathway analysis of genes in the G2 and BPD overlap showed that the most enriched pathways included the p53 signaling pathway and the complement and coagulation cascades. Previous studies have demonstrated a role for p53 in the development of BPD (30). Among the genes identified in this analysis GTSE1, THBS1, and SERPINE1 act downstream from p53.…”
Section: Discussionmentioning
confidence: 68%
“…One common histologic feature is the accumulation of apoptotic neutrophils, epithelial, or parenchymal cells in the inflamed tissues (11,12). This observation is unexpected as apoptotic cells are removed rapidly in healthy adults.…”
mentioning
confidence: 99%
“…(Adapted from Schafer FQ et al, 2001) The link between redox potential and BPD can be explained by an exacerbated apoptosis rate caused by an abnormally elevated redox potential (Luyet et al, 2000). Lung samples from premature baboons with BPD (Das et al, 2004) showed a large number of apoptotic events. In newborn guinea pigs given parenteral nutrition for 4 days, the alveolar count was 20% lower when the nutritive solution was infused without light protection, peroxide concentration being higher in light-exposed solutions (Section 5.2 below) (Lavoie et al, , 2005(Lavoie et al, , 2008.…”
Section: Redox Potential Of Glutathionementioning
confidence: 97%